THE DEVELOPMENT OF MAHARAH KITABAH IN THE MILLENIAL ERA: AN ANALYSIS OF NATIQ BOOK - Alhamda, Hakim Syukri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aims to reveal the methods used in Natiq book in developing sentences, bound expressions, free expressions, and making paragraphs in Arabic papers. Natiq book an alternative learning source for learning maharah kitabah in the millennial era. This research used descriptive analysis methods with the type of library research that utilizes library sources to obtain research data. This study reveals that emerge from this research are developments in learning maharah kitabah, especially first, in writing Arabic expressions; second, making sentences; third, bound expressions, free expressions, and fourth, making paragraphs in Arabic papers. The conclusion is that the presence of the Natiq book volume 3 which is recommended by the Qatar mutanadzir and Saudi Arabian Sheikh and the Indonesian mawapres can be used as an alternative learning materials/source for developing maharah kitabah in Arabic language learning today, especially for religious college students in the Arabic Language Education study program. From the results of the analysis of this textbook, it is clear that with the presence of the Natiq method book volume 3, it is very much a solution to the problems of developing maharah kitabah in Arabic language learning today, especially for religious college students.